1988
DOI: 10.1152/ajpgi.1988.254.5.g741
|View full text |Cite
|
Sign up to set email alerts
|

Changes in jejunal myoelectrical activity during exercise in fed untrained dogs

Abstract: Seven female dogs (15-20 kg) were instrumented with seven bipolar electrodes sutured at 3-cm intervals to the serosal surface of the proximal jejunum and were exercised at different intensities and durations on a motor-driven treadmill. Slow-wave frequency increased (P less than 0.05) from preexercise control during prolonged (90 min) exercise and during recovery after short-term exercise (30 min) at 70% heart rate reserve (HRR). These changes were associated with an increase in core temperature. Spike-burst f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Nausea, no matter how it is induced, appears to be associated with a stereotyped pattern of changes in gastrointestinal motility, which include arrest of gastric emptying, relaxation of the gastric fundus, antral relaxation and tachygastria, inhibition of small intestinal motor activity with premature phase III of the migrating motor complex and powerful retrograde contractions. Exercise can interrupt the pattern of gastrointestinal motor activity in fed dogs (Kenney et al, 1988;Kondo et al, 1994) and humans (Soffer et al, 1991) in a way that resembles that which occurs after nausea and is related to the intensity of exercise. It is possible that disturbed motility during exercise could stimulate vagal afferent nerves to cause nausea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nausea, no matter how it is induced, appears to be associated with a stereotyped pattern of changes in gastrointestinal motility, which include arrest of gastric emptying, relaxation of the gastric fundus, antral relaxation and tachygastria, inhibition of small intestinal motor activity with premature phase III of the migrating motor complex and powerful retrograde contractions. Exercise can interrupt the pattern of gastrointestinal motor activity in fed dogs (Kenney et al, 1988;Kondo et al, 1994) and humans (Soffer et al, 1991) in a way that resembles that which occurs after nausea and is related to the intensity of exercise. It is possible that disturbed motility during exercise could stimulate vagal afferent nerves to cause nausea.…”
Section: Discussionmentioning
confidence: 99%
“…These have suggested that heartburn may be caused by acid reflux (Soffer et al, 1993(Soffer et al, , 1994, and abdominal pain, urge to defecate, and diarrhoea may be related to disturbed gastrointestinal motility (Kenney et al, 1988;Kondo et al, 1994;Soffer et al, 1991) perhaps associated with the decreased blood flow to the gut (Rowell et al, 1964) during exercise. Although the prevalence of nausea during exercise can be as high as 21% (Moses, 1990), the predisposing factors have not been identified.…”
Section: Introductionmentioning
confidence: 99%